Liangxue Jiedu Formula Improves Psoriasis and Dyslipidemia Comorbidity via PI3K/Akt/mTOR Pathway - Xie, Xinran; Zhang, Lei; Li, Xue; Liu, Weihong; Wang, Ping; Lin, Yan; Han, Xuyang; Li, Ping (Frontiers in Pharmacology, 2021)
The pathological mechanism of psoriasis and dyslipidemia comorbidity is unclear, and there are few reports on therapy. By establishing an animal model of ApoE-/- mice induced by imiquimod (IMQ), we tried to explore Liangxue Jiedu formula (LXJDF), a traditional Chinese herb medicine, on psoriasis and dyslipidemia comorbidity through PI3K/Akt/mTOR pathway. The experiment was divided into a control group, a model group, LXJDF high-dose group, LXJDF low-dose group, and a positive drug (Atorvastatin) group. Each group of mice was given continuous oral administration once a day. After three weeks, the mice dorsal were smeared with 62.5 mg of 5% IMQ cream for five consecutive days and continued to be given the corresponding drugs. We observed the effects of LXJDF on skin lesions changes, PASI score, pathological characteristics, blood lipid levels (TC, TG, LDL, HDL, and oxLDL), liver pathology, inflammatory factors in the skin, and the protein expression of PI3K/Akt/mTOR pathway both in skin and liver. The results showed that LXJDF could significantly improve the psoriasiform skin lesions of IMQ-induced ApoE-/- mice, including the reduction of PASI, thinning of epidermal thickness, inhibition of hyperkeratosis and parakeratosis, and inflammatory infiltration in the dermis, and reduced lipid accumulation in the epidermal. LXJDF could regulate blood lipid levels, reduce liver inflammation, and protect the liver. LXJDF could significantly decrease the gene expressions of inflammatory factors IL-17A, IL-23, IL-6, and TNF-α in the skin. LXJDF showed specific inhibition of PI3K, Akt, mTOR protein, and its phosphorylation expressions. In conclusion, LXJDF exerts an intervention effect on psoriasis and dyslipidemia comorbidity via PI3K/Akt/mTOR and its phosphorylation pathway.